O modelo de gestão do empresariado para a educação básica brasileira: embates entre excelência e qualidade social? - Macêdo, Sonayra da Silva Medeiros (2019)
The thesis problematizes the action of the private sector in the definition of policies for Brazilian Basic Education, specifically in management. Based in the argument that the leading role of business groups in the educational field is intensifyingin Brazil, with the establishment of legal and regulatory frameworks that expanded the scope of business to define and implement educational public policies. From this perspective, we analyze the management model defined for public education and theoretical contents that have repercussions in the public space as a quality and excellence reference The research is a qualitative study in the educational field,which we resorted to the analysis of proposals called excellence by the business community, specifically, by one of the most active foundations in the educational scenario, with the Brazilian government, Foundation Itaú Social, which has been publishing documents with emphasis on the leaders’ formation, which they seek to carry out a strategic educational project with reference to the quality of the private sector. We use, as a research technique, content analysis. In this sense, as theoretical-methodological procedures, we conducted a bibliographical study and analysis of laws related to the partnership between the public and private sectors, as well a analyticalstudyof representative documents of the business sector on educational management. We discuss the problematic of the private sector acting in the public space, in the broad context of the relationship between State and civil society, starting from the Gramscian conception of State and the problematical of the role played by civil society in Brazil, since the 1990s, with repercussions in the first decades of the 21st century. We understand that the role of the private sector in education has intensified with the regulation given by the Public-Private Partnership Law in 2004, and with the action of the Third Sector, which imposed a new configuration on the Brazilian public educational management. At the beginning of the 21st century, there is a consolidation of an agenda in which administrative reform and the private sector become central to a quality model based on efficiency and productivity, control of public spending, accountability for results and education. as a service. The documents published as a reference for the public education sector present excellent management proposals that reconfigure the sense of quality and democratic principles of management in the field of education.